2018
DOI: 10.1021/acsanm.8b01215
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Deposited Sol–Gel Based Nanoparticle-Imprinted Matrices for the Size-Selective Detection of Gold Nanoparticles

Abstract: Nanoparticles imprinted matrices (NAIMs) is a new approach, in which nanoparticles (NPs) are imprinted in a matrix followed by their removal to form highly selective voids that can recognize the original NPs. In this study, the effect of a sol–gel matrix on the imprinting and reuptake of gold nanoparticles (AuNPs) is examined. Specifically, indium tin oxide (ITO) films were modified with a positively charged polymer, on which the negatively charged AuNPs stabilized with citrate (AuNPs-cit) were adsorbed. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Furthermore, the matrix should grow controllably from the surface to the solution, which implies that electrografting is an ideal approach for the formation of an electrically insulating matrix . We have already suggested the use of sol–gel electrodeposition, phenol, or aryldiazonium salt (ADS) electrografting . The latter is in particular convenient due to three reasons.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the matrix should grow controllably from the surface to the solution, which implies that electrografting is an ideal approach for the formation of an electrically insulating matrix . We have already suggested the use of sol–gel electrodeposition, phenol, or aryldiazonium salt (ADS) electrografting . The latter is in particular convenient due to three reasons.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The high selectivity achieved was primarily due to size exclusion. More recently, we have demonstrated that the nature of the matrix and its interaction with the imprinted NPs affect their recognition and play a major role. NAIMs are envisioned to enable the assembly of either sensors or separation devices for NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the sensing layer is prepared through the NAIM methodology in which NPs are initially placed on the IDE and a thin film is formed covering the nonoccupied areas between the NPs. Removing the embedded NPs leaves behind cavities, which can reuptake the targeted NPs. …”
Section: Resultsmentioning
confidence: 99%
“…In this respect, the IUPAC recommendation of numerous techniques for NPs characterization should be mentioned, but these require heavy-duty instrumentation . “Nanoparticle-imprinted matrices (NAIM)” is an innovative approach developed in our laboratory for NP sensing. NAIM resembles the well-known molecularly imprinted polymer (MIP) approach. In NAIM, nanocavities with specific size, shape, and chemical composition are formed through imprinting of NPs in soft thin layers. ,, The cavities can then reuptake NPs according to their size and surface properties. Notably, previous studies of NAIM systems were limited to metallic NPs and demonstrated applications only in solutions.…”
mentioning
confidence: 99%
“…In 2014, we started to work on this interesting deposition technique, attracted by the possibility to deposit protective layers on the inner surface of complex metallic substrates. Some papers have been produced [25][26][27][28][29], with very interesting results, but a lot of work is still needed to fully understand and develop this method. Among the scientific aspects awaiting clarification, the structure and density of the layers obtained under basic conditions are quite important, especially looking to applications.…”
Section: Novel Technique For the Deposition Of Thin Coatingsmentioning
confidence: 99%